The difference of situational efficiency and indicators of situational-motoric skills between national teams in the World handball championship - Bajgoric, S.; Djug, M.; Bijedic, N.; Mededovic, S. (Sport Sciences for Health, 2016)
This research focused on the establishment of difference in situational-motoric skills and situational efficacy in defence and offence using audio-visual records of the XIX Junior World Handball Championship 2013, Bosnia and Herzegovina. The differences between players of Bosnian and Herzegovinian national team and the first four placed national teams (Sweden, Spain, France and Croatia) by specific playing positions (left back, centre back and right back) were determined. In the case of situational-motoric skills, two indicators (variables) (total/mean number of sprints from the offence to defence, and the total/mean number of jumps in the offence) were analysed, while in the case of the situational efficacy, one variable (total/mean number of fouls 9 m in the game 1:1) was analysed. To establish partial quantitative differences of variables, the pondered mean difference (MD) was used, as well as significance. Observed results indicated that differences existed in situational-motoric skills and situational efficacy between analysed players, according to player`s positions. Therefore, planning of the training process should be directed to improve technical and tactical elements of handball game and the level of the physical preparation to achieve better results, both individually and as a team. ABSTRACT FROM AUTHOR